Integration of anterior neural plate patterning and morphogenesis by the Wnt signaling pathway. Issue 8 (4th November 2013) - Cavodeassi, Florencia; Zou, Yimin; Salinas, Patricia C.
ABSTRACT Wnts are essential for a multitude of processes during embryonic development and adult homeostasis. The molecular structure of the Wnt pathway is extremely complex, and it keeps growing as new molecular components and novel interactions are uncovered. Recent studies have advanced our understanding on how the diverse molecular outcomes of the Wnt pathway are integrated during organ development, an integration that is also essential, although mechanistically poorly understood, during the formation of the anterior part of the nervous system, the forebrain. In this article, the author has summarized these findings and discussed their implications for forebrain development. A special emphasis has been put forth on studies performed in the zebrafish as this model system has been instrumental for our current understanding of forebrain patterning. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 759–771, 2014